Female Factors related with Infertility and Their Pregnancy Outcome after Intrauterine Insemination: Experience of 790 Cases in Bangladesh - Khanam, Shafeya; Khanam, Rehana; Shuvro, Muqsuda Ashraf; Shati, Morium Faruque; Obayed, Trifa (Journal of Current and Advance Medical Research, 2019)
Background: Several female factors are related with the cause of infertility. Objectives: The purpose of the present study was to assess female factors related with infertility and their pregnancy outcome after intrauterine insemination. Methodology: This prospective cohort study was carried out at a private infertility centre (Central Hospital Limited, Dhaka) in Dhaka city of Bangladesh from January 2012 to December 2017 for a period of 6 years. Infertile couples who already had undergone natural cycles of super-ovulation for six months or whose duration of infertility was more than one year were included. Infertile women were evaluated and the causes of infertility were assessed. The follow up was performed to see the pregnancy outcome. Result: A total number of 790 women were recruited. The mean age with standard deviation of study population was 28.94±5.386 years. Among 790 infertile women 12 women were become pregnant after IUI. Among these 12 women female factors of infertility was present in 8(66.7%) cases and the rest 4(33.3%) cases were absent. However, 778 women could not pregnant after IUI and among these 277(35.6%) cases had the presence of female factors and the rest 501(64.4%) cases had absence of female infertility causes. The presence of female factor had 3.62 (95% CI 1.08-12.12) times more risk to become pregnant among the infertile women after IUI (p=0.026). Among 790 infertile women 285(36.1%) women had presence of female infertility factors. Conclusion: In conclusion female factors are significantly related with infertility and their pregnancy outcome after intrauterine insemination. Journal of Current and Advance Medical Research 2019;6(2):87-91